Professionalism and Entrepreneurial Motivation Correlation with Economic Growth in East Nusa Tenggara - Londa, Yulita; Darmo, Ika Suhartanti; Noor, Laili Savitri; Betan, Abubakar; Suarmanayasa, I Nengah (PT Inovasi Pratama Internasional, 2025)
The purpose of this research is to investigate the correlation between entrepreneurship professionalism and motivation with economic growth in East Nusa Tenggara (NTT). The research methodology employed a descriptive quantitative research method with a population of 50 entrepreneurs, who were also the research sample (saturated sample), located in Manggarai, NTT. The researcher analyzed the correlation between entrepreneurship professionalism and motivation with economic growth in NTT using the product-moment correlation method. Data collection was conducted through literature review and distributing questionnaires to entrepreneurs in Manggarai, NTT. The results of this study indicate a positive correlation between entrepreneurship professionalism and motivation with economic growth in NTT at 3.01%. The analysis score shows that the significance value between entrepreneurship professionalism and economic growth in NTT is 0.003, which is less than the significance level of 0.05. This means that the higher the level of entrepreneurship professionalism in NTT, the greater the possibility of economic growth in the region. Additionally, the results of the test also demonstrate a significant correlation between entrepreneurship motivation and economic growth in Manggarai, NTT, with a significance value of 0.002, which is also less than the significance level of 0.05.